Recent advances in molecular biomarkers for diabetes mellitus: a systematic review. (3rd October 2017) - Lees, Ty; Nassif, Najah; Simpson, Ann; Shad-Kaneez, Fatima; Martiniello-Wilks, Rosetta; Lin, Yiguang; Jones, Allan; Qu, Xianqin; Lal, Sara
Abstract: Context: Diabetes is a growing global metabolic epidemic. Current research is focussing on exploring how the biological processes and clinical outcomes of diabetes are related and developing novel biomarkers to measure these relationships, as this can subsequently improve diagnostic, therapeutic and management capacity. Objective: The objective of this study is to identify the most recent advances in molecular biomarkers of diabetes and directions that warrant further research. Methods: Using a systematic search strategy, the MEDLINE, CINAHL and OVID MEDLINE databases were canvassed for articles that investigated molecular biomarkers for diabetes. Initial selections were made based on article title, whilst final inclusion was informed by a critical appraisal of the full text of each article. Results: The systematic search returned 246 records, of which 113 were unique. Following screening, 29 records were included in the final review. Three main research strategies (the development of novel technologies, broad biomarker panels, and targeted approaches) identified a number of potential biomarkers for diabetes including miR-126, C-reactive protein, 2-aminoadipic acid and betatrophin. Conclusion: The most promising research avenue identified is the detection and quantification of micro RNA. Further, the utilisation of functionalised electrodes as a means to detect biomarker compounds also warrants attention.